Adult-onset immunoglobulin A vasculitis - Megha Amarapur; Sangram Biradar (Wolters Kluwer Medknow Publications, 2021)
We describe a case of adult-onset immunoglobulin A vasculitis (IgA vasculitis) presenting with cutaneous, renal and gastrointestinal manifestations without any evidence of articular involvement. Injection rituximab therapy led to complete resolution of the symptoms. IgA vasculitis is more common in children than in adults. However, in adults, it frequently takes aggressive course as worse renal outcomes compared to children. Systemic steroids are recommended for moderate-to-severe IgA vasculitis. However, upcoming evidence suggests good response with B cell-directed therapies such as rituximab.